Pengaruh Kompetensi, Pendidikan dan Pelatihan terhadap Pengembangan Karir dan Implikasinya Kepada Kinerja Aparatur Sipil Negara pada Biro Umum Setda Provinsi Jambi - Patriosa, Purnawan; Syekh, Saiyid; Yamali, Fakhrul Rozi (Universitas Batanghari, 2024)
The purpose of this study is to describe the competence, education and training, career development and performance of civil servants at the Jambi Provincial Setda General Bureau. Furthermore, analyzing the influence of competence, education and training on career development, analyzing the influence of competency culture, education and training on the performance of civil servants. Career development of ASN performance, competence, education and training through career development of ASN performance. This research uses descriptive and definite research methods, namely the method of surveying a group of people, objects, situations and states of thinking systems to describe and perceive meaningfully. means. systematically follow the facts studied. The control study aimed to test hypotheses about the degree of influence between the variables of this study. This research involved 106 civil servants of the Jambi Provincial Setda General Bureau. The sample of 52 respondents was based on the Slovin formula with 1% confidence. Data was analyzed using SPSS 26.0. The results showed that the competency in high conditions, high education and training, high career development and high work performance of civil servants, competence, education and training were simulated and had a positive and significant impact. Competence, education and training simultaneously and partly have a positive and significant effect on the performance of civil servants, as well as career development have a positive and significant effect on the performance of civil servants at the Jambi Provincial Setda General Bureau.